Subsídios ao planejamento ambiental da Bacia Hidrográfica do rio Benfica, RMB – PA/Brasil - PAUNGARTTEN, Sâmela Patrícia Lima (Universidade Federal do Pará, 2017)
The hydrographic basin of Benfica’s river, located in Belém-PA metropolitan’s region, is presented as an important area for observation of the alteration processes of the landscape, because this unit, in the last thirty years, went through significant transformations, imposed by the dynamics and use of the land. Initially, it presented a rural dynamic and nowadays it is consolidating itself as an urban area, which is being aggravated by the emergence of the problems associated to the growing and development of the cities: sanitation, housing and use of the hydric resources. Front this context, this dissertation has the goal of subsidizing the environmental planning and management of this hydrographic basin. In terms of methodology, it was sought the elaboration of the inventory, environmental diagnosis, prognosis and proposes. In an specific manner, it was executed the analysis of the information, which was referred to the physics’ environment, history of the municipal occupation that includes the hydrographic basin of Benfica’s river, socioeconomic conditions and basic sanitation of the population living in the basin, dynamics of the use and coverage of the soil among the years of 1984, 1993, 1999 and 2009, main environmental problems and environmental politics’ force. The main obtained results show an expressive urban expansion in the hydrographic basin of Benfica’s river in the last 30 years, with different environmental problems, unaccompanied of effective politics of territorial planning. This dynamics totals on a physical unit characterized, especially, by low amplitudes and altimetric slopes, with sedimentological processes over the erosicional. The integration of the physical data of the basin allows the partitioning of itself in two sectors (A and B), characterized, respectively, for presenting bigger environmental problems initiated by the consolidation of the urban sector; and other for having the biggest index